Damage identification and assessment in rc structures using vibration data: a review - Fayyadh, Moatasem Mohammed; Razak, Hashim Abdul (Journal of Civil Engineering and Management, 2013)
Inspection of structural components for damage is essential to decision-making for the maintenance of such structures. There have been many studies to assess the reinforced concrete (RC) structural elements. However, the experimental approach is still based on the conventional static test, which is time-consuming, costly, has intensive equipment and labour requirements and causes major disruptions to the existing use. Modal testing provides an integrated approach, i.e. both local and global characteristics can be ascertained for structural assessment. Depending on the accessibility to damage elements, little or no disruption to the existing use is incurred during testing works. The approach towards structural assessment work provides not only a viable but also a robust, less expensive and powerful alternative to conventional techniques. This paper presents the background of the behaviour of the RC material at different loading and unloading conditions, in order to understand its effect on the modal parameters. The use of modal testing for support stiffness deterioration is highlighted and studies on the use of modal testing for classification of damage source are presented. Studies on the use of modal testing for detection of damage severity and location algorithms and procedures are also presented.